1996
DOI: 10.1074/jbc.271.20.11824
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Expression of HIP, a Novel Heparin/Heparan Sulfate-binding Protein, of Human Uterine Epithelial Cells and Cell Lines

Abstract: ) describes the cloning of a fulllength cDNA corresponding to a candidate cell surface HP/HS interacting protein, HIP, expressed by a variety of human epithelia. A synthetic peptide was synthesized corresponding to an amino acid sequence predicted from the cDNA sequence and used to prepare a rabbit polyclonal antibody. This antibody reacted with a protein with an apparent M r of 24,000 by SDS-polyacrylamide gel electrophoresis that was highly enriched in the 100,000 ؋ g particulate fraction of RL95 cells. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
77
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 51 publications
(82 citation statements)
references
References 35 publications
5
77
0
Order By: Relevance
“…In any case, HA-Hep is substantially enriched for anticoagulant activity and with regard to affinity for AT-III-Sepharose. Cell surface-expressed HIP has been suggested to be involved in Hep͞HS-dependent cell-cell or cell-extracellular matrix interactions (7,8). Results of the current study suggest another possible function of HIP, namely, modulation of blood coagulation activities.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…In any case, HA-Hep is substantially enriched for anticoagulant activity and with regard to affinity for AT-III-Sepharose. Cell surface-expressed HIP has been suggested to be involved in Hep͞HS-dependent cell-cell or cell-extracellular matrix interactions (7,8). Results of the current study suggest another possible function of HIP, namely, modulation of blood coagulation activities.…”
Section: Discussionmentioning
confidence: 55%
“…HIP has been identified in human uterine epithelia and a variety of other human epithelial and endothelial cells (7,8). Analysis of the predicted amino acid sequence of HIP revealed a putative Hep͞HS-binding motif.…”
mentioning
confidence: 99%
“…Collectively, these data indicated that secreted HS from different cell types was insensitive to heparanase digestion. HIP is a recently described cell surface HP/HS-binding protein (25,26) and contains a peptide motif that is capable of discriminating between secreted, cell surface, and ECM forms of HS. 2 Therefore, it was considered that heparanase and HIP peptide might recognize similar motifs in HS.…”
Section: Resultsmentioning
confidence: 99%
“…2 HIP is a novel protein found on the cell surface and is expressed in a cell type-specific fashion (25,26). The intact protein binds HP with high affinity (25,26). Additional studies have demonstrated that HIP peptide recognizes a subset of HP and HS (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation